Preparation, characterization of Bi3O4Cl/g-C3N4 composite and its photocatalytic activity in dye degradation. (August 2017) - Ma, Yueying; Chen, Yijin; Feng, Zhe; Zeng, Lin; Chen, Qianqian; Jin, Risheng; Lu, Yu; Huang, Yong; Wu, Ying; He, Yiming
Highlights: High-efficient Bi3 O4 Cl/g-C3 N4 composite was prepared via a simple method. The Bi3 O4 Cl/g-C3 N4 can degrade RhB 3.8 times faster than g-C3 N4 . The influence factors on the photoactivity of Bi3 O4 Cl/g-C3 N4 were investigated. Abstract: This paper presents a novel composite photocatalyst Bi3 O4 Cl/g-C3 N4 composite which was synthesized by a simple mixing and calcination method. The synthesized composite was applied in photocatalytic degradation of rhodamine B solution under visible light irradiation. Results indicated that the Bi3 O4 Cl/g-C3 N4 showed higher activity than pure g-C3 N4 or Bi3 O4 Cl. The optimal sample presents a degradation rate of 0.019 min −1, which is 1.9 and 3.8 times of Bi3 O4 Cl and g-C3 N4, respectively. Various techniques including thermogravimetric analysis (TG), N2 adsorption, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), UV–vis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and photoluminescence spectroscopy (PL) were applied to investigate the characters of the composite and reveal the origin of the high photocatalytic activity. It is found that the coupling of Bi3 O4 Cl on g-C3 N4 slightly increased the BET surface area of the photocatalyst. However, the main reason for the enhanced photoactivity could be ascribed to the synergetic effect between Bi3 O4 Cl and g-C3 N4 in separating electron and hole pairs.